The Characterization and Application of Two Liquid Crystal Mixtures in the Low THz Region - Andong Zheng (Crystals, 2020)
In the previous work, two new nematic liquid crystal (NLC) mixtures, E7-2 and S200-2, were produced by adding eight LC monomers to two commercial LCs S200 and E7, respectively. At λ = 589 nm, the birefringence (Δn) characteristics of the two LC nematic mixtures E7-2 (Δn = 0.260) and S200-2 (Δn = 0.298) are greater than those of the commercial LC E7 (Δn = 0.224) and S200 (Δn = 0.266). The properties (TN-I, ε//, Δɛ, K11, and K33) of these four NLCs were measured. A double-layer metal loop arrays modulation structure based on metamaterial (MM) metal−dielectric−metal (MDM) was designed and fabricated for use in the THz frequency range. The results show that the LC mixtures E7-2 and S200-2 have greater modulation depth (MD) and less modulation insertion loss (IL) than E7 and S200 at THz frequencies. The results show that LC mixtures have significant potential for designing active tunable LC-based devices in the THz and visible light range.